Turkish Political Islam and its Role in the Geopolitical Complex of the Middle East. - Ioannis Mazis (Geopolitics: theory and praxis., 2002)
Whether or not political islam constitutes a threat for the regime of Turkey -secular by inference- remains an either sincere or hypocritical, yet always invariable, question for the western decision-making and international political influence centres.